2012
DOI: 10.1080/07481187.2011.584024
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Not Trying to Be Cured, So There's Not Much He Can Do for Me”: Hospice Patients’ Constructions of Hospice's Holistic Care Approach in a Biomedical Culture

Abstract: The hospice philosophy was founded on a mission to provide comprehensive and holistic services to individuals at the end of life. Hospice interdisciplinary teams work together to offer therapies such as spiritual services, comfort care, and massage therapy to meet patients' physical, psychological, emotional, and spiritual needs. Although the hospice philosophy is guided toward patient-centered care, limited research has examined how patients understand holistic care services. Through a social constructionist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…2 Hospice use by Medicare recipients alone has grown dramatically over the past decade. 4 However, when cure is no longer possible, hospice care offers a treatment approach that encompasses the physical, emotional, and spiritual needs of patients, using a patient-centered, culturally competent approach. By 2007, this percentage had increased to 30.1%.…”
mentioning
confidence: 99%
“…2 Hospice use by Medicare recipients alone has grown dramatically over the past decade. 4 However, when cure is no longer possible, hospice care offers a treatment approach that encompasses the physical, emotional, and spiritual needs of patients, using a patient-centered, culturally competent approach. By 2007, this percentage had increased to 30.1%.…”
mentioning
confidence: 99%
“…The majority of studies were conducted in North America (n=26),19–44 with 11 from Europe,45–55 7 from Oceania4 56–61 and 6 from Asia 62–67. Participants were sampled from hospice settings (inpatient and hospice at home) in 27 studies,4 19 25 26 28–35 38–40 45–47 53 54 56–58 60–62 66 acute and long-term care settings in 9,22 27 44 55 59 63–65 67 general practices settings in 3,42 48 52 cancer centres in 4,23 24 36 37 a mix of settings in 3 studies21 49 50 and palliative care centres in 2 studies 43 51. One study provided no details on where participants were recruited from 41.…”
Section: Resultsmentioning
confidence: 99%
“…For 10 datasets, studies were included where they reported that the majority of patients (ie, ≥50%) had died within a year or before study completion 23 24 26 27 31 34 36 39 46 59 61. Twenty-one datasets included participants with a mix of chronic conditions,19 21 25 28–33 39–45 47–50 53 54 56–58 61 18 datasets included only participants with cancer,4 20 23 24 26 27 34–37 46 51 52 59 60 62–67 and 1 dataset included participants with only neurodegenerative diseases 55. Two datasets did not specify participants’ conditions 22 38…”
Section: Resultsmentioning
confidence: 99%
“…That is, discourses of death denial and biomedical tendencies toward cure are still circulating in the midst of the hospice movement (Whittington, 2011). This continued focus on survival and overcoming death is evidenced by the fact that the length of time patients are enrolled in hospice is decreasing to a mere 19 or fewer days (U.S. General Accounting Office, 2000), which Pederson and Emmers-Sommer (2012) argue is due to the pervasive biomedical construction of health which opposes hospice's holistic mission and likely impedes early referrals to hospice programs. Furthermore, the total health care cost in the last two months of life is greater than the budget of the Department of Homeland Security or the Department of Education, despite the fact that twenty to thirty percent of these procedures are futile (Kroft, 2010).…”
Section: Illness Narratives and The Eolmentioning
confidence: 99%
“…As discussed in chapter one, the modernist approach legitimizes biomedical knowledge as truth. As Frank (1995) argues, the modernist agenda regards the doctor's chart as the "official story of the illness" (p. 5 (Pederson & Emmers-Sommer, 2012), patients referred to hospice staff when asked about their health care providers, suggesting that patients see hospice as medical intervention.…”
Section: Modernist Ideals Present In Eol Narrativesmentioning
confidence: 99%